La tomaison des albums de Buddy Longway a-t-elle valeur de chapitrage ? - Alain Corbellari (Cahiers de Narratologie)
The twenty albums of Derib's Buddy Longway series, published from 1974 to 2006, present a narrative coherence and a diegetic continuity without example to this degree in French comics. By choosing to kill his hero in the last volume, Derib closes his series without the possibility of prolonging it and incites the reader to reinterpret the global narrative as a single “novel” whose twenty albums would be like successive chapters. We analyze here the modalities and the consequences of this long-term narrative construction.